A scrapbook of child stories as a media to improving the story-telling skill - Fetty Fellasufah; Ali Mustadi (Intelektual Pustaka Media Utama, 2021)
This research aimed to determine the effect of scrapbook child stories as a media for storytelling skills for elementary school students. This type of research was a quasi-experimental quantitative study with a pretest-posttest group design. The population of this research was second grade elementary school students of Candimulyo sub-district, involving two classes as the control class and the experimental class. The test results were then analyzed using the prerequisite test and hypothesis testing. The prerequisite test consists of the normality test using the Kolmogorov Smirnov test and the homogeneity test using the One Way Anova. Hypothesis testing using t-test with independent sample t-test. The results of the analysis were then tested using a significance level of 0.05. The results of this result showed that the control class and the experimental class had a normal and homogeneous distribution. The t-test results showed a significance level of 0.05. It means that there was a significant effect of scrapbook child stories to improve storytelling skills.